Diagnostic accuracy of optic nerve head and macula OCT parameters for detecting glaucoma in eyes with and without high axial myopia - Rezapour, Jasmin; Walker, Evan; Belghith, Akram; Bowd, Chrisotpher; Fazio, Massimo A.; Jiravarnsirikul, Anuwat; Hyman, Leslie; Jonas, Jost B.; Weinreb, Robert N.; Zangwill, Linda M. (American journal of ophthalmology, 2024)
Purpose - To characterize structural differences and assess the diagnostic accuracy of optic nerve head (ONH) and macula optical coherence tomography (OCT) parameters to detect glaucoma in eyes with and without high axial myopia. - Design - Cross-sectional study. - Methods - Three hundred sixty-eight glaucoma and 411 healthy eyes with no axial myopia, 393 glaucoma and 271 healthy eyes with mild axial myopia and 124 glaucoma and 85 healthy eyes with high axial myopia were included. Global and sectoral peripapillary retinal nerve fiber layer thickness (pRNFLT), Bruch's membrane opening minimum rim width (BMO-MRW), ganglion cell inner plexiform layer thickness (GCIPLT), and macula RNFLT (mRNFLT) were compared and the diagnostic accuracy for glaucoma detection was evaluated using the adjusted area under the receiver operating characteristic curve (AUC). - Results - Diagnostic accuracy for ONH and macula parameters to detect glaucoma was generally high and differed by myopia group. For ONH parameters the diagnostic accuracy was highest for global (AUC = 0.95) and inferotemporal (AUC = 0.91) pRNFLT for high myopes and global BMO-MRW for nonmyopes (AUC = 1.0) and mild myopes (AUC = 0.97). For macula parameters, the diagnostic accuracy was higher in high myopes with 6 of the 11 GCIPLT global/sectors having adjusted AUCs > 0.90 compared to nonhigh myopes with no AUCs > 0.90. In all myopia groups, mRNFLT had lower AUCs than GCIPLT. - Conclusions - The diagnostic accuracy for pRNFL and GCIPL was high for high axial myopic eyes and shows promise for glaucoma detection in high myopes. Further analysis is needed to determine whether the high diagnostic accuracy can be confirmed in other populations.